The Impact Of Financial Literacy And Financial Attitudes On Financial Management - Irmayanti Sudirman; Mulyana Machmud; Hartati; Mirna (International Journal of Education Management and Religion, 2026)
: This study examines the influence of financial literacy and financial attitudes on financial management among employees of PT Telkom Akses Parepare. Using a descriptive quantitative method, data were collected from 147 respondents selected through the Slovin formula. Primary data were obtained through questionnaires measured using a Likert scale. The analysis employed validity and reliability tests, multiple linear regression, t-tests, and F-tests using SPSS version 27. The findings reveal that financial literacy does not have a significant partial effect on financial management, indicating that having adequate financial knowledge does not automatically translate into responsible financial behavior. This condition may stem from the gap between understanding and practice, where individuals possess theoretical financial knowledge but do not consistently apply budgeting, saving, or investment discipline due to low motivation, limited self-control, or economic pressures. Conversely, financial attitudes show a positive and significant partial effect on financial management. Individuals with positive financial attitudes—such as discipline, responsibility, and prudent thinking—tend to make wiser financial decisions and manage resources more effectively. Moreover, financial literacy and financial attitudes simultaneously have a significant effect on financial management, with an R² value of 68.6%. This indicates that a substantial proportion of variations in financial management behavior is explained by these two variables. The results highlight the importance of strengthening not only financial knowledge but also affective and behavioral aspects to foster responsible and sustainable financial practices in the workplace. Integrated financial education programs are therefore essential to enhance employees’ capacity to manage finances effectively.